SUBSÍDIOS À PREVENÇÃO E COMBATE A INCÊNDIOS FLORESTAIS COM BASE NO COMPORTAMENTO DA PRECIPITAÇÃO PLUVIOMÉTRICA NA FLORESTA NACIONAL DE IRATI, PARANÁ - Alexandre França Tetto; Antonio Carlos Batista; José Renato Soares Nunes; Ronaldo Viana Soares (Ciência Florestal, 2010)
This research was developed in the Irati National Forest, located predominantly in the county of Fernandes Pinheiro, Paraná State, Brazil, using daily rainfall data from 1963 to 2006. The objective of the study was to examine the precipitation behavior, an important variable in fire occurrence, to use the information in further work on forest fire prevention and control. It was analyzed the monthly precipitation, the number of days with rain, and average daily precipitation, in terms of means, minimum and maximum values. Afterwards, the data were grouped and an analysis of the precipitation evolution for that period was carried out. It was determined and analyzed the inter annual variability of dry and rainy seasons considering the 44 years. Results showed: a) the normal fire season was concentrated from April to August, a period of lower monthly average precipitation; b) an increase in the annual precipitation along the period being studied; c) a decrease in the number of rainy days per year; and d) an increase in the daily average precipitation. It was observed an increase of 128.78 mm in the total annual precipitation, a decrease of approximately 3 days of rain, and an increase of 0.90 mm of average rainfall per day over the period. The beginning of the rain season is oncentrated in the first 20 days of September (70.5%). It was observed equivalence between the dry and rain seasons in 1968, 1978 and 1997, what resulted in a forest fire danger increase.